Evaluation of MONOFER-induced hypersensitive reactions: a retrospective cohort study - Mahreen Muzammil; Ainan Arshad; Ahmed Ayaz; Muhmmad Umair Ihsan; Kashif Hussain; Muhmmad Yasir; Hareem Rehman (Journal of the Pakistan Medical Association, 2022)
Iron deficiency is the most common cause of anaemia. Over the years, various IV preparations of iron have been developed, including Monofer® (Iron isomaltoside 1000), that showed a remarkable reduction in the occurance of hypersensitivity reactions. The main aim of the study was to evaluate the severity and extent to which hypersensitivity reactions occur after the administration of IV iron isomaltoside 1000 in an Asian population. Multistage sampling was adopted for this study. The overall sample size was 864. The mean age of the participants was 55.29 ±18.44 years. The results depicted that 63 (7.29%) of the entire participants faced hypersensitivity reactions after IV administration. A total of 43 (68.25%) of participants who experienced hypersensitivity reactions showed clinical symptoms within one hour, 11(17.46%) showed reaction in 1-3 hours and 9 (14.29%) showed in > 3 Hours. —Continue